ELECTRONIC POCKET BOOK ON DIVERSITY OF WATER PLANTS IN RIVER IRRIGATION RAWA VILLAGE TANIPAH DISTRICT MANDASTANA - Wulan Handayani; Hardiansyah Hardiansyah; Mahrudin Mahrudin (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Plant diversity can be used as learning enrichment material in schools. Likewise, the types of aquatic plants used as enrichment materials in electronic pocket books. This study aims to describe the validity of the electronic pocket book of aquatic plants in the Rawa Irrigation River, Tanipah Village, Mandastana Regency. Research using a descriptive approach with the development of formative evaluation Tessmer (1998) is limited to the stages of development which include self-evaluation, expert review, and content practicality tests. The test results on this product are very valid and very practical. So that it can be used as material to enrich the concept of biodiversity in secondary schools.